Analysis of a resonator with a directional ultrasonic vibration converter of R-L type using the finite elements method - T. GUDRA (Archives of Acoustics)
Some results of the analysis of the R-L type resonator with directional converter using the finite elements method (FEM) are presented in the paper. Three types of resonator tuning result from the analysis and they can be used for converters of other type. The modal patterns in anti-phase and in-phase vibration modes for all types of tuning are presented. The choice of particular tuning depends on the way of using the converter. The modulus of the relation between the surface displacement amplitude for a longitudinal vibrating resonator and the side displacement amplitude for a radial vibrating resonator can be interpreted as the gain coefficient of converter's vibration amplitude. Moreover the influence of rode and disk resonator dimensions on proper frequencies of the converter vibration is described.